Competition Versus Tradition in Kodokan Judo - Ebell, S. Biron (Revista de Artes Marciales Asiáticas, 2012)
Judo’s association with the International Olympic Committee (IOC) and their corporate sponsors is eroding the practice, larger principles, and aims envisioned for Kodokan Judo by its founder, Jigoro Kano. In order to be accessible to a neophyte television audience, judo has had to become a more marketable commodity. These changes, among others, have devalued recreational judo in the minds of some. This paper presents a brief developmental history of judo as it evolved to meet the needs of the IOC.